2023
DOI: 10.1007/s10343-023-00871-y
|View full text |Cite
|
Sign up to set email alerts
|

Effect of Nitrogen Application and Fertigation Scheduling On Potato Yield Performance Under Drip Irrigation System

Abstract: The drip irrigation method offers the potential of higher application efficiency of water and allows precise placement of fertilizer directly in the root zone. The use of drip irrigation also facilitates the frequent application of fertilizer via injection in the irrigation system, which allows the conjunction between nutrient application and time of crop needs. The effect of nitrogen (N) rate and drip fertigation scheduling were evaluated on yield, N uptake, and recovery of potato grown on sandy soil. The N w… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(3 citation statements)
references
References 42 publications
0
3
0
Order By: Relevance
“…US No.1 yields were higher, with three biweekly applications of 44 kg N/ha as compared to six weekly applications of 22 kg N/ha [69]. Badr et al [74] found that weekly drip fertigation of N fertilizer through the crop stage-wise fertigation strategy (N supply partitioned as 12.5, 25, 50, and 12.5% of total N supply at initial, development, mid, and maturation stage, respectively) with 360 kg N/ha increased tuber yield by 13 and 22% as compared to weekly and biweekly equal fertigation strategy, respectively. Errebhi et al [117] discovered that increasing the applied N rates at planting from 0 to 135 kg N/ha significantly increased culls and smallsized tubers while increasing average NO 3 − leaching beyond 140 cm soil depth by 91 kg N/ha for the 'Russet Burbank' potato.…”
Section: Impacts Of N Fertilizer Application Methods On Yield and Yie...mentioning
confidence: 98%
See 2 more Smart Citations
“…US No.1 yields were higher, with three biweekly applications of 44 kg N/ha as compared to six weekly applications of 22 kg N/ha [69]. Badr et al [74] found that weekly drip fertigation of N fertilizer through the crop stage-wise fertigation strategy (N supply partitioned as 12.5, 25, 50, and 12.5% of total N supply at initial, development, mid, and maturation stage, respectively) with 360 kg N/ha increased tuber yield by 13 and 22% as compared to weekly and biweekly equal fertigation strategy, respectively. Errebhi et al [117] discovered that increasing the applied N rates at planting from 0 to 135 kg N/ha significantly increased culls and smallsized tubers while increasing average NO 3 − leaching beyond 140 cm soil depth by 91 kg N/ha for the 'Russet Burbank' potato.…”
Section: Impacts Of N Fertilizer Application Methods On Yield and Yie...mentioning
confidence: 98%
“…The timing of fertilizer application was also found to affect the NUE in potato crops. The weekly fertigation of N fertilizer through crop stage-wise fertigation scheduling had a higher NUE as compared to biweekly crop stage-wise fertigation scheduling and both weekly and biweekly equal fertigation scheduling in 'Cara' potato cultivar [74]. However, Zebarth et al [123] concluded that N fertilization, either at planting or hilling, had no significant impact on NUE during seasons of sufficient soil moisture, but a split application of N could result in reduced nitrogen uptake efficiency during dry seasons.…”
Section: Nitrogen Use Efficiency In Potatomentioning
confidence: 93%
See 1 more Smart Citation